Peoples’ Perception on Invasive Alien Plant Species of Ramdhuni Municipality, Sunsari District, Eastern Nepal - Chaudhary, Sujan; Thapa Magar, Gyanu; Shrestha, Sabitri; Balami, Sujan (Amrit Research Journal, 2022)
The purpose of this study was to record existing information and perception of local people on invasive alien plant species IAPs in the rural areas of lowland, eastern Nepal (Ramdhuni Municipality, Sunsari District). A semi-structured questionnaire survey and interview were carried out to document whether the people were known or unknown to the IAPs followed by harmful or beneficial effects of IAPs and control measures to minimize the spread of IAPs. We found that only 6.25% of respondents knew about the IAPs and there was significant difference between the percentage of respondents who were known or unknown to IAPs. There was a significant positive correlation between the respondents' ages and the number of plants they described. Local people have been using IAPs for food, medicine, and fodder for a long time. However, some IAPs also have detrimental effects in forest and agriculture.